Long Term Results of the Modified Bentall Procedure With Mechanical and Biological Composite Valve Grafts - Werner, Paul; Gritsch, Jasmin; Kaider, Alexandra; Coti, Iuliana; Osorio, Emilio; Mahr, Stephane; Stelzmueller, Marie-Elisabeth; Kocher, Alfred; Laufer, Günther; Andreas, Martin; Ehrlich, Marek (Frontiers in Cardiovascular Medicine, 2022)
Objectives Despite the evident shift toward biological prostheses, the optimal choice of valve remains controversial in composite valve graft (CVG) replacement. We investigated long-term morbidity and mortality after CVG implantation in an all-comer cohort with a subgroup analysis of patients aged 50–70 years stratified after valve type. Methods A total of 507 patients underwent the Bentall procedure with either a mechanical (MCVG, n = 299) or a biological (BCVG n = 208) CVG replacement between 2000 and 2020. A single-center analysis comprising clinical and telephone follow-up was conducted to investigate late mortality and morbidity Results The 30-day mortality in all patients [age 56 ± 14 years, 78.1% male, EuroSCORE II 3.12 (1.7; 7.1)] was 5.9%. Patients who were electively operated on had a 30-day mortality of 1.5% (n = 5) while it remained higher in urgent/emergent procedures (n = 25, 15.4%). Survival at 10 and 15 years was 78.19 ± 2.26% and 72.6 ± 3.2%, respectively. In patients aged 50–70 years (n = 261; MCVG = 151, BCVG = 110), survival did not differ significantly between the valve groups (p = 0.419). Multivariable analysis showed no significant impact of valve type on survival (p = 0.069). A time-varying relation with survival was notable, showing a higher risk in the MCVG group in the early postoperative phase, which declined compared to the BCVG group in the course of follow-up. Conclusions The Bentall technique presents with excellent mortality when performed electively. The type of valve prosthesis showed no statistically significant effect on mortality in patients aged 50–70 years. However, a time-varying relation showing an initially higher risk with MCVG which decreased compared to BCVG at long-term follow-up was notable. Further studies with even longer follow-up of BCVGs will clarify the ideal choice of prosthesis in this patient subset.